(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Sugar cane bagasse can be used as fuel in boilers to produce steam and electricity. After many stages of sugar cane milling process the byproduct bagasse is available in solid form with higher percentage moisture content. The length of smaller sized bagasse named as pith is varied from 2mm to 6mm. The process of separating larger size of bagasse and smaller one is known as depithing. The burning smaller size particle of bagasse is called as pith, and it can be used as fuel in the power plant boilers. Due to high moisture content (48% to 52%) the pith needs excess amount of air or oxygen for attaining complete burning. If sufficient amount of air is not supplied slower rate of burning takes place. The slower rate of burning is due to utilizing some amount of heat to evaporate the water vapors presents. This process is called as removal of latent heat of vaporization. This loss of heat energy to evaporate water reduces the boiler efficiency. A multiple stage fluidized bed dryer is one of the bagasse dryer to accelerate the evaporation of moisture content at faster rate. The hot air passing through the bagasse removes the surface water content. The fluidized bed dryer consists of two or three stages of drying process containing rectangular and circular shaped distributor pipe connected with the wall of the vertical dryer through extended pipes at four sides contains many number of nozzles.. The counter current flow of bagasse and hot air induces the removal of moisture content over the surface of the bagasse. The latent heat of evaporation is accelerated in faster rate with the help of separate mechanical device which agitate the bagasse between the holding tray and the distributor.